Maxilla bone evaluation and implant surgical planning in a periodontal disease patient - Queijo, Luis (2014)
Knowing the value of biomodeling techniques - associating medical image segmentation with additive manufacturing, as a complimentary diagnose mean in the bone evaluation in complex and sensible anatomical areas (Queijo et al., 2010) it has been possible to support the diagnostic of a 50 years old female patient suffering from periodontitis who has lost an large amount of maxilla bone. At same time, by determining quantity and quality of maxilla bone in the affected area, the surgical planning have been made recurring to complete and fractioned biomodels in order to correctly define implants placement.